Climate-driven changes to taste and aroma determining metabolites in an economically valuable portunid (Portunus armatus) have implications for future harvesting - Champion, Curtis; Frank, Damian; Taylor, Matthew C.; Kaczmarska, Kornelia; Piyasiri, Udayasika; Broadhurst, Matt K.; Shalders, Tanika C.; Coleman, Melinda A. (Frontiers in Marine Science, 2022)
The effects of climate change on the distribution and biology of fisheries species have received substantial attention, but quantitative assessments of changes to taste and aroma determining compounds remain limited—despite sensory quality being a key driver of demand for most harvested species. Utilising the economically important blue swimmer crab (Portunus armatus), we tested the effects of temperature and salinity treatments aligned with near-future climate change projections on volatile and non-volatile sensory compounds that determine seafood flavour. Volatile compounds were analysed using solid phase microextraction and gas chromatography-mass spectrometry and non-volatiles were identified using liquid chromatography (mass spectrometry analysis). Multivariate analysis revealed that temperature, but not salinity, significantly affected the compositions of both volatile and non-volatile compounds in crab meat following a 30-day exposure period. Univariate analyses highlighted significant reductions in amino acids and amines associated with bitter and sweet organoleptic properties following exposure to elevated temperature. These results imply the potential for climate change to alter taste and aroma determining compounds in seafood, which could affect future harvesting priorities. Assessments of seafood sensory quality under climate change can produce valuable information to help predict shifts in future effort among harvested species that form the basis of important global fisheries.